THE PORTRAIT OF FAILURE OF THE BOURGEOISIE IN GUSTAVE FLAUBERT’S MADAME BOVARY - Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2018)
The research aims to discuss the social class in French society, that is, Bourgeoisie. The objectives of the research are to portray the failure of bourgeoisie in Gustave Flaubert’s Madam Bovary and the effects of the failure of bourgeoisie toward two main characters, Emma Bovary and Charles Bovary. The main theories that are used to analyze the data are Marxism, bourgeoisie and setting. While, the method of the research is descriptive method and library research is used as the technique of collecting data. There are four approaches used, that is, moral and philosophical approach, historical biographical approach, psychological approach and sociological approach. The findings of the research are failure of bourgeoisie when Flaubert mocks the bourgeois class’s pretensions to knowledge and learning and its faith in the power of technologies that it does not completely understand. Emma becomes discontented and rebellious, while Charles is devoted to Emma and ashamed of his downfall.